Electrochemical Nitrogen Reduction Reaction on Noble Metal Catalysts in Proton and Hydroxide Exchange Membrane Electrolyzers. Issue 14 (29th December 2017) - Nash, Jared; Yang, Xuan; Anibal, Jacob; Wang, Junhua; Yan, Yushan; Xu, Bingjun
Abstract : Five noble metal catalysts (Pt/C, Ir/C, Pd/C, Ru/C, and Au/C) are evaluated for electrochemical nitrogen reduction reaction (ENRR) to produce ammonia in both proton exchange membrane (PEM) and hydroxide exchange membrane (HEM) electrolyzers (PEMELs and HEMELs). The competing hydrogen evolution reaction (HER) is found to be the dominant reaction on all catalysts tested in both PEMELS and HEMELs, which is consistent with recent computational predictions that metallic catalysts are unlikely to be selective for ENRR. With the increase of applied potentials, the rate of HER increase significantly, which suppresses the ENRR, leading to significant decreases of faradaic efficiencies. Leaching of quaternary ammonium from HEM is found to interfere with ammonia quantification, which necessitates a pretreatment protocol. Due to the relatively slow kinetics of HER in alkaline solution, faradaic efficiencies in HEMELs are generally higher than those in PEMELs. We believe that these results provide a solid baseline for future research on ENRR in both PEMELs and HEMELs.